Development of the Leapfrog Group's Bar Code Medication Administration Standard to Address Hospital Inpatient Medication Safety. Issue 6 (7th September 2022) - Austin, J. Matthew; Bane, Anne; Gooder, Valerie; Saltsman, Connie; Wilson, Marisa; Stewart, Kathryn Burggraf; Derk, Jordan; Danforth, Melissa; Michalek, Christina
Abstract: Medication errors are the most common type of error in hospitals and reflect a leading cause of avoidable harm to patients. Bar code medication administration (BCMA) systems are a technology designed to help intercept medication errors at the point of medication administration. This article describes the process of developing, testing, and refining a standard for BCMA adoption and use in U.S. hospitals, as measured through the Leapfrog Hospital Survey. Building on the published literature and an expert panel's collective experience in studying, implementing, and using BCMA systems, the expert panel recommended a standard with 4 key domains. Leapfrog's BCMA standard provides hospitals with a "how-to guide" on what best practice looks like for using BCMA to ensure safe medication administration at the bedside.